2009
DOI: 10.1002/lapl.200810086
|View full text |Cite
|
Sign up to set email alerts
|

Low threshold and efficient multi-wavelength Brillouinerbium fiber laser incorporating a fiber Bragg grating filter with intra-cavity pre-amplified Brillouin pump

Abstract: Abstract:A low threshold and efficient multi-wavelength Brillouin-erbium fiber laser with a pre-amplified Brillouin pump within a Fabry-Perot cavity is presented. With the utilization of a fiber Bragg grating filter as one of the fiber loop mirrors, up to 25 stable Brillouin Stokes lines could be generated with channel spacing of 0.088 nm. The architecture of the design consumes only 3 dBm of the Brillouin pump power and 90 mW of the 980 nm laser diode to produce the 25 maximum output channels. The signal to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Yusoff et al [3] only demonstrated a single wavelength operation of BFL. Compared to other reported multi-wavelength Brillouin/erbium fiber laser with a much longer SMF and EDF [9,10], however, the proposed BFL has a relatively smaller number of lines.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Yusoff et al [3] only demonstrated a single wavelength operation of BFL. Compared to other reported multi-wavelength Brillouin/erbium fiber laser with a much longer SMF and EDF [9,10], however, the proposed BFL has a relatively smaller number of lines.…”
Section: Resultsmentioning
confidence: 86%
“…SBS is a nonlinear effect resulting from the interaction between intense pump light and acoustic waves in a medium and giving rise to backward propagating frequency-shifted light [1]. BFLs are a coherent light source that has been attracted significant interest for decades due to their linewidth narrowing effect [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid multi-wavelength Brillouin and erbium fiber lasers (MWBEFLs) have been widely investigated as they are particularly interesting because of their low power threshold [21], large tunability [5,16,22] and ability to generate many Brillouin shifted frequencies [23,24]. Their basic principle is to combine the narrow nonlinear gain offered by SBS in an undoped fiber with the broadband linear gain from an erbium doped fiber to enable the cascaded processes of SBS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the required use of multiple lasers complicates practical applications owing to their high cost. Therefore, previous work has developed an economic method for producing an array of lasers through the means of using a multiwavelength fiber laser source [9][10][11][12][13][14][15][16][17][18][19]. However, achieving a reconfiguration capability for the transfer function is extremely difficult since the wavelength spacing of optical sources is fixed, explaining why obtaining a simple and adjustable multi-wavelength light source is a challenging task.…”
Section: Introductionmentioning
confidence: 99%